Central executive authorities of Ukraine on air traffic services - Юринець, Юлія Леонідівна; Мазурик, Світлана Анатоліївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2017)
A system of central executive power bodies of Ukraine on air traffic services. Update their legal and administrative status and the means of influencing the management of air traffic. Analyzes the system of normative legal acts in this area. In particular, it was found that the basic legislative acts of Ukraine in the field of civil aviation is the Law of Ukraine of 10.11.1994 number 232/94-VR «On Transport» and the Air Code of Ukraine, the first edition of which adopted 05.04.1993. At the same time noted that the system of regulations, which were at that time, did not meet fully this act of higher legal force. The current system of central authorities in the aviation sector created under the Decree of the President of Ukraine of 09.12.2010 p. № 1085/2010 «On optimization of central authorities". This system includes the Ministry of Infrastructure of Ukraine and the State Aviation Administration of Ukraine. However, with the adoption of the Air Code of Ukraine of 19.05.2011 in the version of a system of executive bodies began to contradict this version of the Code has not been aligned with him. In particular, the provisions of these bodies contain no clear definition of which authorities deemed authorized executive body in the field of state aviation within the meaning of Article 5 of the Air Code of Ukraine. Instead, the analysis of aggregate powers allow argue that such authority is the State Aviation Administration of Ukraine. Attention is also drawn simultaneously with the new provisions of these central authorities, adopted by the Cabinet of Ministers of Ukraine continues to be valid and previous Regulation approved by Decree of the President of Ukraine. However, the regulation in these Regulations (relatively the same agencies) is pairs controversial. The system powers of the State Aviation Service of Ukraine in the field of air traffic services provided by the Regulations on the use of airspace Ukraine approved by the Cabinet of Ministers of Ukraine of 29.03.2002 № 401. Comparing the norms of the Tax Code of Ukraine concerning the relevant authority confirms that these powers are inherent Authorized Agency. The system of air traffic control service and unified civil-military system of air traffic of Ukraine. Indicated that normalization of some components of the system does not meet the prescribed manner regulation. According to the research concludes that the administrative regulation of air traffic services characterized by inconsistency, regulations that were made, were often subjective, contradictory, and sometimes the law.